HOW TO MEASURE GAIN-SHARING IN AN OUTSOURCING RELATIONSHIP: A CASE STUDY IN INFORMATION TECHNOLOGY ENVIRONMENT - Guerreiro, Reinaldo; Pereira, Carlos Alberto; Agrawal, Surendra (Revista Eletrônica de Administração, 2013)
This study aims to approach the issue of gain-sharing measurement in an information technology outsourcing relationship as a component of remuneration policies for contracted services among companies. The methodology encompass three steps: (i) bibliographical revision on outsourcing relationship in information technology environment and pricing in outsourcing decisions; (ii) a case study in which the problem of gain-sharing measurement emerges in the relationship (providing information technology services) between two large-scale international companies that operate in Brazilian credit card market; (iii) discussion of the findings of the case study on basis of the revised literature. The contributions of the paper are: (i) to identify the main issues related to outsourcing decisions and pricing in outsourcing relationship; (ii) to present a description of the characteristics and behavior of costs in information technology environment; and (iii) to provide an analysis and discussion about the method adopted by the companies for gain-sharing measurement. The bibliographical research showed a lack of literature  regarding to the specific subject of gain-sharing measurement. The findings of the empirical study indicated that information technology companies are highly structured with fixed costs and that gain-sharing method adopted by studied companies corresponds to cost efficiency measured through budget parameters.